Avrupa sermaye piyasalarının bütünleşme yönünde yeniden yapılanması ve Türk sermaye piyasalarının Avrupa sermaye piyasalarına entegrasyonu - Muğaloğlu, Yusuf İzettin (My University, 2002)
Sermaye piyasaları; tasarruf fazlası bulunan ekonomik birimler ile fon açığı bulunan ekonomik birimlerin karşı karşıya geldiği ve fon açığı olan birimlerin bu gereksinimlerini fon fazlası olan birimlerden sağlamalarına imkan veren finansal piyasaların bir bölümünü oluşturmaktadır. Pazar ekonomisini benimsemiş endüstrileşmiş veya endüstrileşmekte olan ülkelerde yatırım için uzun vadeli fonlara ihtiyaç vardır. Bu ihtiyacı daha kısa vadeli fon arzı sağlayan para piyasalarının karşılayamaması sermaye piyasalarının oluşmasına ve gelişmesine olanak sağlamıştır. Böylece sermaye piyasaları, para piyasaları ile birlikte finansal piyasaların bir alt bölümü olarak yerini almıştır. Bu çalışmanın birinci bölümünde finansal piyasalar; finansal piyasaların birer alt bölümü olan para piyasaları ve özellikle de sermaye piyasaları teorik olarak incelenmiştir. Sermaye piyasası faaliyetleri, araçları ve kurumları tanıtılarak, sermaye piyasasının kavramsal çerçevesi oluşturulmuştur. Tezin ikinci bölümünde entegre olma yönünde hızlı adımlar atan Avrupa Sermaye Piyasaları ele alınmış; Avrupa Birliği'nde sermaye piyasalarının genel yapısı, gelişimi ve bütünleşme süreci ayrıntılı bir şekilde ortaya konmuştur. Avrupa Birliği'nde sermaye piyasalarının bütünleşme süreci yasal düzenlemeler ve uygulama boyutu olmak üzere iki boyutta incelenmiştir. Avrupa Birliği sermaye piyasalarındaki bu bütünleşme süreci Avrupa Birliği'ne üye olmayı hedefleyen ve aday statüsü kazanan Türkiye'yi de yakından ilgilendirmektedir. Bu aşamada, Türk Sermaye Piyasalarının teknik ve yasal çerçeve açısından Avrupa Sermaye Piyasaları ile uyumlu olması büyük önem taşımaktadır. Bu bağlamda, tezin üçüncü bölümünde Türk Semaye Piyasalarının genel özellikleri, Avrupa Sermaye Piyasalarına uyumun gerekçeleri, uyum için yapılan yasal düzenlemeler ve yapılması gerekenler ele alınmıştır. Sonuç olarak, bu tez Avrupa Sermaye Piyasalarında devam etmekte olan bütünleşme ve yeniden yapılanma kapsamında Türk sermaye piyasalarının Avrupa sermaye piyasaları ile bütünleşme sürecinin uygulama boyutuna taşınabilmesi için yapılan değerlendirmeler ve somut öneriler ile sonuçlandırılmıştır.

While recovering from a severe economic crisis, Turkey has to manage economic, political and social challenges of the near future. From now on, the main route of Turkey, which is expected to take Turkey to full integration into the European Union (EU), is going to be shaped by the implementation of two major governmental programs. The first one is the macroeconomic adjustment program made with International Monetary Fund (IMF), which includes the implementation of the structural economic reforms. The second one is the National Program that covers the reconstruction of the social, political and legal framework in the light of the EU. The first program aims at overcoming the outstanding problems of the Turkish economy and providing the sustainable economic growth whereas the second one aims at the full integration of the country into the EU. In this paper, in addition to these existing programs of the government, we propose a complemantary strategy which would be put into action by the Istanbul Stock Exchange (ISE) and would facilitate the integration of the Turkish capital markets into the European capital markets, as a small but crucial part of the full integration. We hope that this proposal would offer a new vision for the ISE and new financing tools for the Small and Medium Size Enterprises (SMEs). In the first part of this paper, we focus on the economic panorama of the country that includes the economic growth, foreign trade, capital flows, prices, public finance and debt stock. In this part, statistical data is given in order to reveal the outstanding problems and the effects of the severe economic crisis. In the light of these data, we assert that the main outstanding problems are unsustainable economic growth, chronic foreign trade deficit, fluctuations in capital flows, high and persistant inflation, unbeareble debt stock and heavy reliance on the banks regarding the public finance. In the second part, we look at the financial sector including both the banking sector and the capital markets in detail. Regarding the banking sector, we see that after the financial crises in November 2000 and February 2001, most of the banks lost their capitals, or were affected seriously. Thus, they could not perform their primary function of extending credits to the private real sector. In the capital markets part, we examine the leading role of the ISE in the Turkish capital markets. We state that introduction of the stock market together with the bonds market offered a new financing tool for the private real sector. However, we claim that disappearance of the private sector bonds after 1994 is a clear indication of the crowding out effect of the government bonds, and significant increase in the trading volume of the bonds market does not mean a real development. We indicate that the ISE needs new vision which would lead the ISE to a real progress. In the third part of this paper, the major problems of the economy and envisaged strategies in the economic program to overcome these problems are summarized. We argue that the economic growth is not sustainable, since high public sector borrowing rate (PSBR), together with the high inflation, prevents the private real sector from financing its investments neither from the banks nor capital markets. We remind that efficient use of capital markets is as important as banking sector in financing the private real sector and specifically point out that capital markets are completely ignored in the economic program of the government. In the light of this analysis, our proposal in the forth part aims at providing the efficient use of capital markets as a stimulus to the economic growth as well as extending the ISE's range of markets, products and investors. In order to provide a strategy which would lead us to this goal, we focus on the importance of the SMEs in the Turkish economy and their financing problems. In order to provide them with a new financing tool via the ISE, first we suggest the inroduction of the SME show room (SMESR), which is totally a new concept developed in this paper, together with integration into the European capital markets. Second, regarding the integration into the European capital markets, we analyze the strengths and weaknesses of the ISE, and propose that the ISE should sign a cross-membership and cross-trading agreement with Euronext, otherwise with Athens Stock Exchage. Then, we determine the steps of an action plan to be implemented by the ISE for both the introduction of the SME show room and integration into the European capital markets. Finally, we conclude that the ISE can play a crucial role in integrating the Turkish capital markets into the European capital markets. This integration would have a notable effect on the ISE, on the SMEs and national capital market infrastructure. The ISE efforts regarding the SMEs' financing and integration into the European capital markets would also provide the efficient use of capital markets as a stimulus to the economic growth.
Keywords: Avrupa Topluluğu-entegrasyon; Sermaye Hareketleri Türkiye